Über einige Typen der Gattung Dusona Cameron (Hymenoptera: Ichneumonidae). - Hinz, Rolf (Contributions to Entomology = Beiträge zur Entomologie, 1963)
As a result of his studies on the type material of the Thomson, Holmgren, Brauns, and Kiss collections the author presents a revision of some types of the Ichneumonid genus Dusona Cam. (Campoplex auct.). Nomenclatural Acts thomsoni Hinz, 1963 (Dusona), spec. n.